Wound-directed revascularisation in the Diabetic Foot patients - N. Kononenko; A. Sheikhali (Journal of Education, Health and Sport, 2016)
Introduction: Peripheral arterial diseases in patients with diabetic foot have significant features in pathogenesis, manifestations and course compared with peripheral arterial disease. These features require different approaches to treatment and the the angiosome theory can help increase the effectiveness of revascularization in patients with diabetic foot.